Pillared Clays and Related Catalysts - Gil, Antonio; Korili, Sophia A.; Trujillano, Raquel; Vicente, Miguel Angel (Springer New York : Imprint: Springer, 2010)
Since the first works introducing the aluminum intercalated clay family in the early 1970s, interest in the synthesis of pillared interlayered clays has increased tremendously, especially research into the properties and applications of new synthesis methods. The need for solids that could be used as cracking catalysts with larger pores than zeolitic materials has spurred the synthesis of new porous materials from clays. This book reviews the properties and applications of pillared clays and other layered materials used as catalysts, focusing on: - the acidity of pillared clays and the effect it has on catalytic performance - the use of pillared clays as supports for catalytically active phases, and the use of the resulting solids in environmentally friendly reactions - the comparison between the reactions of pillared clays and anionic clays.